Modulation of IL-10 production by CD3/CD55 induced Type 1 regulatory (Tr1) T-cells - Musarrat, Tajkia (2019)
A healthy immune system is maintained in a state of balance between pro-inflammatory and anti-inflammatory cells. The paradigm for T-cell activation requires CD80/86:CD28 engagement resulting in differentiation of CD4+ T-helper cells. However, alternative costimulatory molecules may favour the induction of alternate T cell phenotypes such as Type 1 Regulatory (Tr1) T-cells. One such receptor-ligand pair is CD55-CD97. We have previously demonstrated that co-stimulation by CD3/CD55 results in the differentiation of naive CD4+ T-cells into Tr1 phenotype, defined as IL-10+, IFN-- and IL-4-. IL-10 is the predominant immune-suppressive cytokine produced by adaptive immune system and it is required for immune resolution, promoting tolerance and controlling autoimmunity. Considering the importance of IL-10 production in auto-immune diseases, we aimed to study the CD3/CD55 mediated IL-10 production in Multiple sclerosis (MS) patients. In our pilot study, CD3/CD55 stimulation of naïve CD4+ T-cells resulted in significantly lower level IL-10 production as well as lower number of IL-10+ Tr1 cells in MS patients compared to heathy donors. We further investigated the effect of MS associated immune-modulators on the CD3/CD55 mediated IL-10 production. Vitamin-D3 and Dexamethasone preferentially enhanced IL-10 secretion and increased the number of Tr1 cells following CD3/CD55 stimulation whereas IFN- demonstrated similar effect with both CD55 and CD28 costimulation.